Estimation of gillnet and hook selectivity for Carangoides fulvoguttatus (Forsskal, 1775) captured off Kanyakumari coast of India - Balasubramanian, A.; Meenakumari, B.; Pravin, P.; Dhanapal, K.; Boobendranath, M. R.; Erzini, K. (Indian Journal of Fisheries, 2016)
Selectivity and fishing powers of multi-mesh gillnets with mesh sizes of 13.5, 14, 14.5 and 15 cm and hooks No. 5, 6, 7 and 8 were studied using the experimental catch data of the carangid Carangoides fulvoguttatus. (Forsskal, 1775). The selectivity curves, parameters and residual plots for different models viz., normal scale, normal location, log-normal, gamma and bi-normal models were produced applying the SELECT (Share Each Length Class Total) methodology which has been incorporated in the software GILLNET (Generalised Including Log-Linear N Estimation Technique). The models were evaluated using the statistical tools viz., model deviance, dispersion parameter and residual plots to determine the best fit of the selectivity data. The uni-normal model, normal scale was found as best fit for the gillnet catch data while bi-normal was identified as suitable model for the hook catch data. The mesh size of 14.5 cm and hook No. 5 performed better than the other modeled meshes and hooks respectively. Gillnet selectivity data did not converge into bi-normal model due to single mode of capture. However, the hook catch data converged into bi-normal model with two modes of selection curve. Over dispersion was found common in catch data obtained from both gears due to larger size of fishes caught and demonstrated lack of fit in both selection data.